The Nonlinear Acoustoelectric Effect in a Superlattice - Bau, Nguyen Quang; Hieu, Nguyen Van; Thuy, Nguyen Thi; Phong, Tran Cong (Communications in Physics, 2012)
The acoustoelectric effect in a superlattice (SL) is investigated for an acoustic wave whose wavelength λ =2π/ q is smaller than the mean free path l of the electrons and hypersound in the region ql1. (where q is the acoustic wave number) . A nonlinear dependence of the acoustoelectric current j^ac on the constant electric field E is obtained by using the classical Boltzmann kenetic equation. The analytical expression for the acoustoelectric current j^ac is calculated for constant of momentum relaxation time. Numerical calculations is done, and the result is discussed for a typical GaAs/AlGaAs SL. It is noted that when the electric field is negative the current j^ac decreases, reaches a minimum and rises. On the other hand, when the electric field is positive the current increases, reaches a maximum and then falls off. A similar observation has been noted for an acoustoelectric interaction in a multilayered structure resulting from the analysis of Si/SiO_2 structure. The dominant mechanism for such a behavior is attributed to the periodicity of the energy spectrum of electron along the SL axis